TINGKAT KEAKTIFAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA MELALUI APLIKASI EDMODO DI SMK MUHAMMADIYAH 1 BANTUL - Eva Nur Fathonah; Selvia Heryati (Jurnal Komposisi, 2020)
The Covid-19 pandemic has an impact on the world of education, especially in the learning process. Learning that was originally done offline has now had to move online. So e-learning based learning media can be a solution in helping the teaching and learning process, one of which is the Edmodo application.This article will discuss the results of research on the effect of Edmodo as a learning platform related to the effectiveness of online learning at SMK Muhammadiyah 1 Bantul. The research object was the students of class XII RPL 1, XII TKRO 3, XII RPL 2, XII TKRO 4. This research was conducted with a purposive method. While the data collection techniques used were observation and documentation. The results of this study indicate that Edmodo is quite well accepted as an online learning medium. Beside that, Edmodo has many advantages, especially in terms of the features offered so that it can help educators, students, and even parents in online learning.